Leadership and Resistance - Rimay, Deborah (My University, 2018)
Identity and resistance in social work leadership is a fairly recent area in the study of leadership. A significant amount of the literature discusses leadership, identity and resistance from the standpoint of managerialism, where the leader’s character is defined by their response to managing and eliminating staff workplace resistance. This study offers a contrasting approach to the managerial notions of leadership, identity and resistance. This study examines social work leadership in the context of the justice-oriented resistance work leaders do and how their identities inform the strategies they engage. A small qualitative study was done from a critical perspective to better understand how social work leaders in the social services engage in resistance work when encountering social injustices in their organization. The findings were organized around three central themes form the interviews. The first theme was how the participants understood resistance or what were they fighting for in their work. Participants were fighting for respectful relationships with service users, and fighting against the implications of social inequalities embedded in policies and directives that are not beneficial to service users. The second theme focused on the strategies the participants engaged in their resistance work. Participants identified the deliberate use of language, awareness and activation of values, and the use of their power and role as leaders. The third theme was how their identities influenced the resistance work they engaged in. The participants drew on their personal histories which have framed their identities to inform the manner in which they resist: to take up certain value positions in their work, to be critical and unafraid in their resistance, and to have strong loyalties to their communities. The results of this study extend the literature on leadership by highlighting resistance not in a passive manner but in the sense of consciously taking actions with consequences. It was apparent the participants engaged in micro political actions and adopted strategies to counter the negative effects of policies and attitudes that promote social inequalities.
Keywords: Leadership; Resistance